2018
DOI: 10.2134/cftm2017.07.0047
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Plant Response Differences among High‐ and Average‐Yield Soybean Areas in Arkansas

Abstract: Core Ideas Crop yield contests provide a unique research opportunity. Planting date is highly related to yield across yield contest sites. An early soybean production system is advantageous for high yields. Increasing soybean [Glycine max (L.) Merr.] yields requires a multi‐pronged approach. Annual state soybean yield contest fields can provide information about yield potentials and plant response differences between high and average‐yield producing areas. The objectives of this study were to i) assess plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This was due to the G × E interaction so that each soybean varieties response differently to each soil types (Alam et al, 2019). The relationship between productivity and soil was very complex and highly dependent on the physical, chemical and biological nature of the soil and external factors (Adams, 2016;Sys et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…This was due to the G × E interaction so that each soybean varieties response differently to each soil types (Alam et al, 2019). The relationship between productivity and soil was very complex and highly dependent on the physical, chemical and biological nature of the soil and external factors (Adams, 2016;Sys et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate, using an average harvest index of 0.53 for Arkansas rice (Karki et al., 2021) and the average grain yield from this study (9.79 Mg ha −1 ) (Table 2), there was roughly 5000 kg straw residue ha −1 left in the field after harvest. In comparison with a rice‐soybean rotation and assuming a harvest index of 0.37 (Adams et al., 2018) and average soybean yield (www.uaex.uada.edu, 2022) of 3.360 Mg ha −1 , there would be only about 1000 kg residue ha −1 remaining in the field after the soybean phase of rotation. Additionally, the amount of soybean residue left during the fallow period is likely less because soybean residues decompose faster than rice straw (Gilmour et al., 1998; Nishimura et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, earlier planting dates have been conclusively demonstrated to be associated with increased seed yield for the Midsouth region (Salmeron et al, 2014), with early indeterminate MG4 genotypes providing the highest and most stable seed yield (Salmeron et al, 2014;Salmerón et al, 2016). Because of the demonstrated benefits of the ESPS, adoption of this method has been increasing among producers in the Midsouth region (Adams et al, 2018). Seed development is more vulnerable to elevated temperatures than vegetative tissues (Fukushima, Kusano, Redestig, Arita, & Saito, 2009) and the reproductive optimum for soybean has been reported to be between 22 and 24˚C (Hatfield et al, 2011).…”
Section: Core Ideasmentioning
confidence: 99%
“…In recent studies, earlier planting dates have been conclusively demonstrated to be associated with increased seed yield for the Midsouth region (Salmeron et al., 2014), with early indeterminate MG4 genotypes providing the highest and most stable seed yield (Salmeron et al., 2014; Salmerón et al., 2016). Because of the demonstrated benefits of the ESPS, adoption of this method has been increasing among producers in the Midsouth region (Adams et al., 2018).…”
Section: Introductionmentioning
confidence: 99%